The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.12693/aphyspola.131.1525
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Monitoring during Focused Ultrasound Treatment by Means of the Homodyned K Distribution

Abstract: Temperature monitoring is essential for various medical treatments. In this work, we investigate the impact of temperature on backscattered ultrasound echo statistics during a high intensity focused ultrasound treatment. A tissue mimicking phantom was heated with a spherical ultrasonic transducer up to 56 • C in order to imitate tissue necrosis. During the heating, an imaging scanner was used to acquire backscattered echoes from the heated region. These data was then modeled with the homodyned K distribution. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…The results showed that the shape parameter of the K distribution was the best marker of temperature variations. Byra et al 61 used the homodyned-K distribution to model the RF envelope collected during HIFU heating of tissue phantoms in vitro. It was found that a combination of echo mean intensity and the effective number of scatterers per resolution cell was the best temperature indicator.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The results showed that the shape parameter of the K distribution was the best marker of temperature variations. Byra et al 61 used the homodyned-K distribution to model the RF envelope collected during HIFU heating of tissue phantoms in vitro. It was found that a combination of echo mean intensity and the effective number of scatterers per resolution cell was the best temperature indicator.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…The HK model has been applied to characterizing cell pellet biophantoms [43], tissue phantom heated by focused ultrasound [44], reperfused infarcted porcine myocardium in vivo [45], mice breast cancer in vivo [46], human breast lesions in vivo [47,48], response of advanced human breast cancer to neoadjuvant chemotherapy in vivo [49], cancerous human lymph nodes ex vivo [50], porcine red blood cell aggregation ex vivo [51], human carotid artery plaque in vivo [52], human skin ulcer ex vivo [53], nonalcoholic steatohepatitis of rats in vivo [54], and hepatic steatosis of rabbit livers ex vivo [55] and rat livers in vivo [20]. Using a rat model, Ghoshal et al [55] demonstrated that there is a significant increase in the HK µ parameter with increasing fat content in the liver samples.…”
Section: Ultatrasound Homodyned-k Imagingmentioning
confidence: 99%
“…1,4 Therefore, with the development of effective parameter estimators, the HK model has been used in ultrasound parametric imaging for various medical applications, such as classification of breast lesions, temperature monitoring during focused ultrasound treatment, and hepatic steatosis evaluation. 2,7,21,29 -31…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Therefore, with the development of effective parameter estimators, the HK model has been used in ultrasound parametric imaging for various medical applications, such as classification of breast lesions, temperature monitoring during focused ultrasound treatment, and hepatic steatosis evaluation. 2,7,21,[29][30][31] To estimate the parameters of the statistical distribution models, methods based on maximum likelihood estimator (MLE), moments, or artificial neural networks (ANNs) are commonly adopted. For the HK distribution, Dutt and Greenleaf 32 first proposed a method based on the moments of the intensity (i.e., MI estimator).…”
Section: Introductionmentioning
confidence: 99%